2007
DOI: 10.1007/s10578-007-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylphenidate and Bupropion on DHEA-S and Cortisol Plasma Levels in Attention-deficit Hyperactivity Disorder

Abstract: We evaluated plasma levels of DHEA-S and cortisol before and after treating ADHD patients with one of two medications: methylphenidate (n = 12) or bupropion (n = 10). Boys with ADHD (combined type) were evaluated with the Korean ADHD rating scale (K-ARS) and the computerized ADHD diagnostic system (ADS). All assessments were measured at baseline and repeated after 12 weeks. There were significant clinical improvements in both treatment groups as measured by K-ARS and ADS. DHEA-S levels increased from baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…In the present study many of the children and adolescents with PAE + ELA reported medication use at study enrollment (primarily stimulant and non-stimulant medications typically prescribed for ADHD, and atypical antipsychotics, as noted), and these children showed significantly lower morning cortisol levels compared to both children with PAE + ELA who were not taking medications and controls. Findings from studies examining the effects of these types of medications on cortisol levels are mixed, showing either elevated basal cortisol levels or no effects (Isaksson, Hogmark, Nilsson, & Lindblad, 2013; Lee et al, 2008; Wang, Huang, Hsiao, & Chen, 2012). At least one study has shown an opposite pattern of findings in children with combined-type ADHD, with more typical morning cortisol levels in children taking stimulant medications, and depressed morning levels in those untreated (Kariyawasam, Zaw, & Handley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study many of the children and adolescents with PAE + ELA reported medication use at study enrollment (primarily stimulant and non-stimulant medications typically prescribed for ADHD, and atypical antipsychotics, as noted), and these children showed significantly lower morning cortisol levels compared to both children with PAE + ELA who were not taking medications and controls. Findings from studies examining the effects of these types of medications on cortisol levels are mixed, showing either elevated basal cortisol levels or no effects (Isaksson, Hogmark, Nilsson, & Lindblad, 2013; Lee et al, 2008; Wang, Huang, Hsiao, & Chen, 2012). At least one study has shown an opposite pattern of findings in children with combined-type ADHD, with more typical morning cortisol levels in children taking stimulant medications, and depressed morning levels in those untreated (Kariyawasam, Zaw, & Handley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We did not collect any information on medication use prior to sample collection days. Several medications used to treat common childhood behavior problems influence sex hormone levels (Hibel et al 2007; Lee et al 2008), although it is unknown to what extent these effects persists beyond medication use. Similarly, we did not obtain information on menstrual cycles in females, although roughly half the sample reported having started menstruating.…”
Section: Discussionmentioning
confidence: 99%
“…MPH treatment may lead to several adverse effects, including decreased appetite, sleep disturbance, headache, anxiety, irritability, and rarely occurring cardiovascular adverse events (Cortese et al, 2013; Martinez-Raga et al, 2013). Moreover, researchers have noticed that MPH treatment potentially affects the endocrine system of patients (Maayan et al, 2003; Lee et al, 2008; Wang et al, 2011, 2014). More recently, controversies have emerged regarding whether MPH interferes with the gonadal function of children, particularly testosterone levels.…”
Section: Introductionmentioning
confidence: 99%